Probability function of fatigue crack growth in case of material overloading - Gubeljak, Nenad (Kovine zlitine tehnologije, 1998)
Studies of structural components under a fatigue environment including overloads are rather interesting in engineering practice today. One important task is to determine the probability distribution function in consideration of two failure modes by a selected fatigue load and overload level. The probability density function permits to evaluate of overloading under fatigue environment on the residual life or to predict the failure of a component. The fatigue crack propagation in case of overloading can be modeled by the Markov's process. The obtained probability functions describe the probability of retarded crack growth propagation as a consequence of the overload cycle.
Keywords: trdnost; razpoka; utrujenost materialov; verjetnostni račun